The Implementation And Obstacles of Intercultural Awareness in Learning English for Elementary Students - Dessy Dwisusila; Agustina Agustina; Jufrizal Jufrizal (Universitas Lancang Kuning, 2023)
It is impossible to study a language without also studying its culture. When learning a language, intercultural sensitivity is necessary. Because English is taught to primary school pupils at a relatively young age, it is expected that studying English will instill international awareness. Data were gathered at several Bangkinang City elementary schools through observation, interviews, and documentation of chosen samples using purposive sampling methods. The results show that: (1) intercultural sensitivity has been applied in the teaching of English to elementary school students; (2) cultural learning is still taught in an integrated and implicit way; and (3) the challenges are the shortage of teachers, the characteristics of young students, the lack of a curriculum that explicitly supports cultural learning, and the limited resources. For pupils to develop into proficient intercultural speakers and engage in intercultural communication at a young age, instructors, and institutions of higher learning must improve the integration of intercultural sensitivity into English language instruction at the elementary school level.